The association between genotype and BMI, health and lifestyle indicators as well as weight loss outcomes in overweight/obese Caucasian adults - Harbron, Janetta (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Physiological Sciences))--University of Stellenbosch, 2011.